IMPROVING THE FINANCING MECHANISM OF PRESCHOOL EDUCATIONAL ORGANIZATIONS IN UZBEKISTAN - Nasurova Kamolaxon Ravshanovna (American Journals, 2023)
This article discusses the problems of evaluating the quality of educational activities in preschool educational institutions and methodological approaches to evaluating the effectiveness of budget expenditures on education based on the analysis available in world practice.
Keywords: Preschool education, funding, efficiency, budgetary resources.